Ampliação dos poderes judiciais nas ações coletivas : em busca da concretização do acesso à ordem jurídica justa - Oliveira, Alex Maia Esmeraldo de (2016)
This dissertation aims to demonstrate how the expansion of instructive powers of the judge, under the collective process, is an appropriate mechanism to densify access to the legal system, calling it the attributes of equity and effectiveness. To give support to this proposal, it is through the theoretical contributions of post-positivism as a promising paradigm proper legal foundation, through the legal argument at the time that it reveals an instrument of control and improvement of judicial decisions. On the other hand, the proposal places the collective protection in the second renewals wave of civil procedure, describing the extra-legal obstacles to access to jurisdiction and analyzes the constitutional postulate in its material dimension, pointing out the risk of its sacredness and its negative impact on the protection of collective goods. The collective process is raised to the status of an autonomous branch of the civil process, composing a microsystem endowed with natural principles. When entering your analysis describes its social and political relevance, underlying having a society permeated by massed relations. As a theoretical reference the expansion of instructive powers leaned over the device and inquisitorial systems. This polarization emerges a discussion of the role of the judiciary. We propose a new perspective of judicial action, more dynamic and embedded in the social environment that surrounds it, a position aligned with the publicist view of the process. In this context it works with a new process model, cooperative, a convergent analysis with collective protection, enhancing its democratic foundation and its contribution to the delivery of a fair and appropriate remedy. The powers are described in kind, highlighting the paradigms in consumeristas and environmental labors. The right to trial was submitted to a constitutional reading to support their investment and modulation inspired by the nature of the legal interests at stake. The theory of dynamic distribution is presented as strengthening the judicial action in favor of the effectiveness of collective action. They are faced limits to this outburst, with the goals of the constitutional process principles. Given these assumptions, the outlook point-of attracting organized civil society to make use of collective actions, from the strengthening of judicial functions aimed to eradicate the barriers of access to the differentiated protection.